Analysis Effect of Corporate Social Responsibility on the Company Value in LQ45 Index - Rhis Ogie Dewandaru*; Ali Akbar Anggara (Universitas Syiah Kuala, 2023)
The purpose of this study is to examine the impact of CSR on the list of companies that are listed as LQ45 companies on the Indonesian stock exchange, Bursa Efek Indonesia (BEI). The method used in this study with a quantitative descriptive approach. According to the results of the data analysis that has been done, it can be inferred that corporate social responsibility has a negative, significant impact on a company's legal structure. This is demonstrated by the CSR threshold value of -70.024, which is less than Table 2,048; and the CSR significance value of 0.049, which is less than 0.05